Catalytic Degraders Effectively Address Kinase Site Mutations in EML4-ALK Oncogenic Fusions - Gao, Yang; Jiang, Baishan; Kim, Hellen; Berberich, Matthew J; Che, Jianwei; Donovan, Katherine A; Hatcher, John M; Huerta, Fidel; Kwiatkowski, Nicholas P; Liu, Yingpeng; Liuni, Peter P; Metivier, Rebecca J; et al. (Journal of medicinal chemistry, 2023)
Heterobifunctional degraders, known as proteolysis targeting chimeras (PROTACs), theoretically possess a catalytic mode-of-action, yet few studies have either confirmed or exploited this potential advantage of event-driven pharmacology. Degraders of oncogenic EML4-ALK fusions were developed by conjugating ALK inhibitors to cereblon ligands. Simultaneous optimization of pharmacology and compound properties using ternary complex modeling and physicochemical considerations yielded multiple catalytic degraders that were more resilient to clinically relevant ATP-binding site mutations than kinase inhibitor drugs. Our strategy culminated in the design of the orally bioavailable derivative CPD-1224 that avoided hemolysis (a feature of detergent-like PROTACs), degraded the otherwise recalcitrant mutant L1196M/G1202R in vivo, and commensurately slowed tumor growth, while the third generation ALK inhibitor drug lorlatinib had no effect. These results validate our original therapeutic hypothesis by exemplifying opportunities for catalytic degraders to proactively address binding site resistant mutations in cancer.